ENHANCING PRONUNCIATION SKILLS OF ENGLISH LANGUAGE LEARNERS (ELLS) THROUGH ENGLISH FILMS. - Abdullaeva Gulkhayo (Western European Studies, 2025)
This paper will explore the effective use of English-language films as a tool for improving the pronunciation skills of English Language Learners (ELLs). Obviously, engaging with authentic dialogues, diverse accents, and speech patterns in movies can make the learning process more enjoyable and interesting for the learners. Specific strategies for using films, such as focused listening exercises, repetition of dialogue, and role-playing activities, as well as the advantages of visual aids in helping comprehension will be discussed. Moreover, the work will highlight the significance of choosing appropriate films that cater to different language levels and interests. Through this approach, ELLs can build confidence in their pronunciation while also gaining cultural insights and expanding their vocabulary
Keywords: Pronunciation; films; authentic; dialogues